METHOD TO INVESTIGATE FICTIONAL ENTITIES: A CASE OF ISHINOMORI SHOTARO’S “KAMENRIDER BLACK” TV SERIES IN INDONESIA - Rizki Musthafa Arisun (STBA LIA - Jakarta, 2018)
This article reports an experiment to pursue appropriate observation method on fictional entities inside popular culture products from Japan: two dimensional characters, fictional characters in a movie. Previous research showed how Indonesian popular culture producers being empowered in production, as fictional entities involved, such as “Hatsune Miku” (HM), a virtual singer persona. This article focused on older cases where media Japan travelled to Indonesia. Back in 1989, a TV action serial